Current acute stroke trials and their potential impact on the therapeutic time window. (February 2012) - Schellinger, Peter D; Köhrmann, Martin
Several trials in acute stroke are underway or have been completed recently. Among the latter, ECASS 3 was a milestone regarding the extension of the rigid 3-h time window out to 4.5 h for intravenous thrombolysis with recombinant tissue plasminogen activator. Several other approaches are being tested for thrombolytic therapy, among them modern imaging-based patient selection of patients and interventional approaches. Other pharmaceutical strategies include neuroprotection, and restoration, biophysical approaches, such as near infrared laser therapy, hemodynamic augmentation, and sphenopalatine ganglion stimulation. This perspective will cover the recently completed and currently recruiting acute stroke trials with respect to their potential role in expanding the therapeutic time window for acute ischemic stroke.